Assessment on the consequences of injection strategies on combustion process and particle size distributions in Euro VI medium-duty diesel engine. (April 2020) - Bermúdez, Vicente; García, Antonio; Villalta, David; Soto, Lian
Although there are already several works where the influence of injection parameters on exhaust emissions, and specifically on particulate matter emissions, in diesel engines has been evaluated, the diversity in the results that can be found in the literature indicates the need to carry out new experiments that can provide more information about the influence of these parameters on modern diesel engines. This study intends to be placed within this scientific framework, hence a parametric study was carried out based on the independent modification of the main injection timing and the injection pressure with respect to the nominal conditions of a new Euro VI direct injection diesel engine. Four steady-state operation points of the engine map were chosen: 25% load and 950 r/min, 50% load and 1500 r/min, 75% load and 2000 r/min and 100% load and 2200 r/min, where in each of these operation points, the variations of the injection parameters in the study on the combustion process and its consequent impact on the particle size distribution, including an analysis of the geometric mean diameter values, were evaluated. The results showed that the different injection strategies adopted, despite not significantly affecting the engine efficiency, did cause a significant impact on particle number emissions. At the low load operation, the size distribution showed a bimodal structure, and as the main injection timing was delayed and the injection pressure was decreased, the nucleation-mode particle concentration decreased, while the accumulation-mode particle concentration increased. In addition, at medium load, the nucleation-mode particle emission decreased considerably while the accumulation-mode particle emission increased, and this increase was much greater with the main injection timing delay and the injection pressure reduction. Similar behavior was observed at high load, but with a much more prominent pattern.